2011
DOI: 10.1159/000328233
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 Plasma Levels and Outcome after Ischemic Stroke

Abstract: Background: Growth differentiation factor 15 (GDF-15) is a stress-responsive cytokine that is induced after experimental brain injury. We hypothesized that the circulating levels of GDF-15 are increased and associated with neurological outcome in patients with ischemic stroke. Methods: Serial blood samples were obtained between 6 h and 7 days after symptom onset in 57 consecutive patients with acute ischemic stroke (n = 51) or transient ischemic attack (n = 6). GDF-15 was measured by immunoradiometric assay. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 72 publications
3
24
0
Order By: Relevance
“…GDF-15 is secreted at low concentrations from most tissues but may be overexpressed in cardiomyocytes and various vascular cell types under stressful conditions (1 ). Several recent investigations have demonstrated that circulating GDF-15 concentrations are increased and independently prognostic across a wide spectrum of cardiovascular diseases, including acute and chronic coronary artery disease, congestive heart failure, and ischemic stroke (2)(3)(4)(5)(6).…”
Section: © 2013 American Association For Clinical Chemistrymentioning
confidence: 99%
“…GDF-15 is secreted at low concentrations from most tissues but may be overexpressed in cardiomyocytes and various vascular cell types under stressful conditions (1 ). Several recent investigations have demonstrated that circulating GDF-15 concentrations are increased and independently prognostic across a wide spectrum of cardiovascular diseases, including acute and chronic coronary artery disease, congestive heart failure, and ischemic stroke (2)(3)(4)(5)(6).…”
Section: © 2013 American Association For Clinical Chemistrymentioning
confidence: 99%
“…For example, elevated serum concentrations of growth differentiation factor 15 are associated with an unfavourable outcome after ischaemic stroke [56]. To date, there are only two stress markers that independently predict functional outcome and mortality: copeptin, a fragment of provasopressin, and midregional pro-atrial natriuretic peptide (MR-proANP).…”
Section: Immune and Stress Markers For The Prediction Of Long-term Oumentioning
confidence: 99%
“…10, 11 GDF-15 has also been reported to improve prediction of the risk of incident overall cardiovascular disease (CVD), heart failure, and cancer, as well as all-cause and cancer-related mortality in community-based cohorts. 12, 13 Higher GDF-15 concentrations have been noted with increasing age and in smokers, persons with diabetes, hypertension, poor kidney function, and low high-density lipoprotein cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%